In Pursuit for Legitimacy: An Overview of Contemporary Policing in Indonesia - Rio Adhikara; Panji Yugo Putranto; Abraham Ben Gurion (Eduvest - Journal of Universal Studies, 2024)
The Indonesian National Police (Polri) is currently placing a fair amount of concern on the state of its police legitimacy. However, numerous evidence of public response to date indicated some problems that threaten the legitimacy of Polri and might affect their performance. Following the public response, Polri launched several significant alterations to its policing methods. Hence, several critics questioned the effectiveness of Polri’s current method. This study will examine the pros and cons of the new policing scheme taken by Polri based on literature review of previous studies. Some suggestions as an alternative method are also provided in this study to improve Polri’s approach. Implications of these findings for police practitioners and researchers are then discussed.